Sewage Sludge Compost as Potting Media Component for ivy Pelargonium (Pelargonium peltatum (L.) L’Her.) Production - Agnieszka Zawadzińska; Piotr Salachna (Journal of Basic & Applied Sciences, 2014)
The increasing demand and raising cost of high quality peat for horticultural use have led to search for low cost substrates as an alternative. The source of materials for their production can be various types of industrial, municipal and agricultural waste. Most of them are rich in organic matter and minerals essential for plant growth. The aim of the study was to evaluate the growth and flowering of two ivy pelargonium cultivars (‘Beach’ and ‘Boneta’) grown in the media containing sphagnum peat and composts made from municipal sewage sludge and structure-forming components. Two different types of composts were used, consisting in equal proportions of sewage sludge and straw (SSRS) or leaves (SSL). The composts replaced 25% or 12.5% of sphagnum peat (v/v) in the growth media. A control media was sphagnum peat (100%) supplemented with a mixed fertilizer. It was found that the media containing both types of compost might be useful for growing ivy pelargonium. The most beneficial effect on the growth, foliage, and a decorative value of the pelargonium was observed for the medium containing 12.5% of SSL compost and 87.5% of peat. Decorative value of the pelargonium grown in the medium with 25% of SSL compost or with either dose of SSRS compost, did not differ from the control plants. The investigated cultivars differed in the number of shoot, color and area of leaves as well as length of stem of inflorescence. ‘Boneta’ cv. developed more stems and had greener leaves than those from ’Beach’ cultivar. While cultivar ‘Beach’ had greater area of leaves per plant and longer stem of inflorescence.